CO2 reforming of methane over Ta-promoted Ni/ZSM-5 fibre-like catalyst: Insights on deactivation behavior and optimization using response surface methodology (RSM). (15th February 2021) - Hambali, H.U.; Jalil, A.A.; Abdulrasheed, A.A.; Siang, T.J.; Owgi, A.H.K.; Aziz, F.F.A.
Graphical abstract: Highlight: Fibre-like Ni-Ta catalyst was prepared by microemulsion and impregnation method. Ta was evaluated as an effective promoter under different feeding compositions. Addition of Ta increases the rate of reactants dissociation and carbon gasification. Small-size and immobilized Ni sites led to strong catalytic stability. Optimum CH4 conversion of 96.6% at T = 784.15 °C, CO2 :CH4 ratio = 2.52 and GHSV = 33760 mL g −1 h −1 . Abstract: The catalytic performance of fibre-like Ta-promoted Ni/ZSM-5 in dry reforming of methane (DRM) was studied under different feeding compositions for obtaining a robust catalyst, which is important for large-scale production of syngas via DRM. The deactivation of unpromoted Ni/ZSM-5 was due to polymerization of carbon deposits which block the active sites and accelerate agglomeration. Introduction of Ta was shown to facilitate the rate of dissociation of reactants and carbon gasification due to increased Ni-support interaction and surface oxygen species. From ANOVA analysis, operating temperature was found to be the most significant operating parameter that influence CH4 conversion. The optimum CH4 conversion predicted from the response surface analysis is 96.6% at reaction temperature of 784.15 °C, CO2 :CH4 feed ratio of 2.52, and GHSV of 33, 760 mL g −1 h −1 . The strong catalytic stability is a result of the small-size and immobilized Ni sites which is vital for efficient DRM catalyst development.